Properties and biodegradability of waste paper filled polyurethane foams composites - Dahlia, Zakaria (Universiti Malaysia Perlis, 2011)
The research is focused to study the properties of polyurethane foam reinforced with different types and content of waste paper. The comparison of the effects of three types of waste paper, such as paper sludge (PS), old newspaper (ONP) and office white paper (OWP) on physical, mechanical, thermal, biodegradable properties and morphology of PU foam was studied. The result show ONP foam significantly highest value of compressive strength, compressive modulus and hardness compared than PS and OWP foam composites. The increasing filler loading improved the mechanical properties but reduced the density of foam. Scanning electron microscopy (SEM) study indicated that the addition of waste paper in polyurethane foam reduced the open cell structure of foam. The biodegradation study of waste paper foam composites increased with increasing of waste paper loading. However, the ONP foam composites showed higher degradation in soil compared to the OWP foam and followed by PS foam composites. The results of thermogravimetric analysis (TGA) showed PS foam composites has highest thermal stability compared with OWP and ONP foam composites. The PS foam composites exhibit the highest of crystallization. The presence of the triethylene diamine (TEDA) as catalyst has improved the compressive strength, compressive modulus, hardness and density of waste paper foam composites. The thermal stability of waste paper foam composites with TEDA is higher than waste paper foam composites without TEDA. The micrographs of waste paper foam composites with TEDA show the addition of filler and catalyst can affect the crosslinking of the foam composites to produce the smaller cell structure. The waste paper foam composites with methylene chloride (MC) have higher of compressive strength, compressive modulus and hardness but lower the density and thermal stability compare to waste paper foam composites without MC. The morphology of waste paper foam composites with different filler loading with MC show smaller open cell compared to without catalyst. Partial replacement of toluene diisocyanate (TDI) in diphenyl methane 4,4’- diisocyanate (MDI) of ONP foam indicates higher compressive strength, compressive modulus, hardness and density compared to MDI/ONP foam composites. The micrograph of TDI/MDI/ONP foam composites show that the foam close cell structure compared to MDI/ONP foam composites. The TDI/MDI/ONP foam composites have better thermal stability than MDI/ONP foam composites.